Recommendations for the Development of CFD Model to Assess the Thrombogenic Potential of Stents - Stiehm Michael; Borowski Finja; Oldenburg Jan; Öner Alper; Schmitz Klaus-Peter (Current Directions in Biomedical Engineering, 2022)
Computational fluid dynamics (CFD) has enormous potential for the development of novel cardiovascular implants. In particular, the evaluation of the thrombogenic potential of implants is gaining importance. For this purpose, the numerical model must represent the essential properties of the real system, i.e., an implant in the human blood circulation, in a suitable form. Due to its complexity, the model building process is crucial for the successful application of the model. Currently, there is no structured guideline for the application of numerical flow simulation to which model developers can refer. Based on NASA and ASTM, we present key aspects of the model building process using CFD for stent flow as an example.